(untitled) (Journal of history, 2019)
Тhe article is devoted to the dendrochronological analysis of archaeological wood from the monuments of Pazyryk culture.Relative dendrochronological Dating was performed on the basis of the obtained tree-ring chronologies.There were also conducted studies of cores from live trees, which were harvested in the sample areas Tuyuksu, Big Almaty lake and Gorelnik. The species composition of wood and the possibility of using the obtained chronologies for the reconstruction of the climate were studied.The absolute radial increment graphs for each radius were plotted from the annular chronologies, which are used to accurately date the annual rings. The maximum age of the studied plants living trees spruce spruce is 229 years pertaining to the sample area Tuyuksu.The maximum width of the annual rings for all the studied objects is 9.4 mm, which indicates good weather conditions during the active growth and development of the plant. Average width of annual rings for spruce Shrenk in plots of Big Almaty lake is of 2.15 mm.Logs from the scientific-restoration laboratory “Island of Crimea” were processed and studied. 124, 130 and 141 year tree-ring chronologies were found on the sawn trees, the age of the trees is from 124 years to 141 years.